Foreign Venture Capital Firm - Skye in China. - Hu, XiaoRui (2007)
The reasons of why Tom Skype paid more attention to Venture Capital management have received more and more attentions from academic researchers in many current business studies. Based upon one case study in the Skype, this research has analyzed the significant of the Venture Capital. This research listed some differences of the situations in for the Skype and how it set up the Venture Capital strategic in China, then gave the author's own opinions to the research question.